POTENSI ROTAN KAWASAN HUTAN PRODUKSI DI DESA UEKULI KECAMATAN TOJO KABUPATEN TOJO UNA-UNA - Y. Amu, Syaiful Y.; Harijanto, Herman; Sudhartono, Arief; Labiro, Elhayat (Universitas Tadulako, 2021)
In Indonesia, there are eight genera of rattan consisting of approximately 306 species, only 51 species have been used. This means that the utilization of rattan species is still low and limited to species whose benefits are known and sold in the market. It is estimated that more than 516 species of rattan are found in Southeast Asia, originating from 8 genera, namely for the genus Calamus 333 species, Daemonorops 122 species, Khorthalsia 30 species, Plectocomia 10 species, Plectocomiopsis 10 species, Calopspatha 2 species, Bejaudia 1 species and Ceratolobus 6 Of the 8 genera, two rattan genera with high economic value are Calamus and Daemonorops. The purpose of this study was to determine the potential of rattan in the Production Forest Area in Uekuli Village, Tojo District, Tojo Una-Una Regency. This study uses the